Teorija dvigatel'noj kompetencii v figurnom katanii - Tiskov, Ju. N. (Teorija i Praktika fiziceskoj Kul'tury, 2003)
The author has attempted to present the new concept of figure skater training program's construction. The conclusions and guidelines formulated in the article were made on the basis of the long-term researches of the author in the area of sports pedagogics and professional activity in the national figure skating team of Belarus and Krasnoyarsk region. The author tenders to look at one implementation of this experience in a new fashion. He had created a new form of organization of training process of the ice skater on the basis of the theory of the key motor competence, not disclaiming the experience accumulated by sports pedagogics for many years.